The Influence of Leg Shape on Thermoelectric Performance Under Constant Temperature and Heat Flux Boundary Conditions - Şişik, Bengisu; LeBlanc, Saniya (Frontiers in Materials, 2020)
Thermoelectric devices offer the potential to convert wasted heat into electricity, and they can be used for thermal management by pumping heat. The advent of new manufacturing techniques such as additive manufacturing enables customizable thermoelectric device shapes. However, there is little knowledge about what shapes are beneficial in applications with differing thermal conditions. This work determines the effect of different thermoelectric leg designs on thermoelectric device performance. Various leg shapes (rectangular prisms, prisms with interior hollows, trapezoids, hourglass, and Y-shape) were modeled numerically to determine their thermal and electrical performance under constant temperature and heat flux boundary conditions. Two thermoelectric materials, bismuth telluride and silicon germanium, were modeled to capture both low and high temperature application cases, respectively. An hourglass-shaped thermoelectric leg with a constant hot side temperature, has the best thermal and electrical performance. The hourglass-shaped leg results in more than double the electrical potential and maximum power compared to the conventional rectangular shape when the cold side experiences a natural convection boundary condition. With a constant hot side heat flux, a reverse trapezoid-shaped leg results in almost double the electrical potential and a 50% increase in the power output compared to the conventional leg shape. In particular, this work shows that considering leg shape alone is insufficient: varying boundary conditions (which reflect different device operating conditions) result in different performance values for the same leg shapes. These findings underscore the importance of leg geometry on electrical and thermal performance of a thermoelectric leg, as well as the importance of considering the device operating condition when selecting the best leg shape.